2016
DOI: 10.1111/apa.13441
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis of parenteral nutrition‐associated cholestasis in extremely low birth weight infants

Abstract: PNAC was common in ELBW infants, was associated with various clinical factors and increased the risk of mortality. However, we did not observe the protective effect of FOLP against PNAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
3
13
1
Order By: Relevance
“…This may be due to the sample size consistent with a previous similar‐sized study wherein multiple regression modeling demonstrated that duration of PN was the only significant predictor of PNAC . Our study confirms associations between both sepsis and prolonged PN and PNAC . Mortality rates for SIP and NEC were as expected, and the lack of increased mortality with PNAC is consistent with published data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be due to the sample size consistent with a previous similar‐sized study wherein multiple regression modeling demonstrated that duration of PN was the only significant predictor of PNAC . Our study confirms associations between both sepsis and prolonged PN and PNAC . Mortality rates for SIP and NEC were as expected, and the lack of increased mortality with PNAC is consistent with published data.…”
Section: Discussionsupporting
confidence: 91%
“…Mortality rates for SIP and NEC were as expected, and the lack of increased mortality with PNAC is consistent with published data. Several studies have noted an increased risk of PNAC in premature infants with NEC with perforation …”
Section: Discussionmentioning
confidence: 99%
“…First, the PN duration (23 days, range: 18-32 days) of the PNAC group was shorter than previous studies. 1,[14][15][16][17] Second, infants in our study received lower doses of lipids (1.5 g/kg/day, range: 1.2-1.8 g/kg/day), 1,[16][17][18] as well as glucose (8.8 g/kg/day, range: 7.1-10.7 g/kg/day) ,1,19,20 which have been reported to be independent risk factors for PNAC. 1,7,14,18 Finally, we excluded infants who underwent surgery, who have a higher risk of developing PNAC.…”
Section: Incidence Of Pnacmentioning
confidence: 66%
“…1,7,14,18 Finally, we excluded infants who underwent surgery, who have a higher risk of developing PNAC. 4,7,20 Risk factor of PNAC Prematurity and low birthweight (LBW) are defined as risk factors of PNAC in some studies, 15,20,21 which are physiologically likely a result of the immature hepatic excretion of premature infants. 22 It is difficult to separate prematurity, birthweight and duration of PN because prematurity and LBW generally need a longer administration of PN.…”
Section: Incidence Of Pnacmentioning
confidence: 99%
“…With regard to monitoring, we again found significant differences across recommendations depending on specimen type (capillary or venous), previous lead result, and lead result trends over time. Most guidance sources Arkansas [40], North Dakota [41], Wyoming [42] Lead Level ≥ 3 μg/dL (1) New Hampshire [43,44] Lead Level ≥ 5 μg/dL b (37) Alabama [45], Alaska [46], Arizona [47,48], California [49,50], Colorado [51,52], Connecticut [53,54], District of Columbia [55,56], Georgia [57][58][59], Hawaii [60,61], Idaho [62,63], Illinois [64,65], Iowa [66,67], Kentucky [68,69], Louisiana [70][71][72], Maine [73,74], Maryland [75], Massachusetts [76][77][78][79], Michigan [80,81], Minnesota [82,83], Mississippi [84,85], Montana…”
Section: Follow-up Testingmentioning
confidence: 99%